INVENTARISASI AMFIBI RESORT CISARUA TAMAN NASIONAL GUNUNG GEDE PANGRANGO BERDASARKAN MUSIM YANG BERBEDA - Agus Pambudi Dharma; Meitiyani Meitiyani (Jurnal Biosilampari : Jurnal Biologi, 2019)
This study aims to inventory amphibians in the Cimisblung Resort Cisarua Gede Pangrango National Park (TNGGP) the rainy season and dry season. Amphibian data collection was carried out in February - August 2019 in and night (19.00 - 23.00 WIB) days using a visual encounter survey method along 500 meters with the river flow aquatic) and terrestrial among others, below the surface of litter, rock, weathered wood, and in the bush. Amphibians were to view and record their morphology, then matched the images with amphibian identification books. After the next step was identified, the amphibian was photographed for documentation. If amphibians are not identified in the field, the amphibians are taken to the Cibinong Zoology LIPI to be identified. The results obtained were 13 species (Leptobrachium haseltii, Megophrys montana, Duttaphrynus melanostictus, Leptophyryne cruentata, Rhacoporus javanus, Philautus aurifasciatus, dan Nycxtixalus margaritifer, Rana calconata, Huia masonii, Oddorana hosii, Limnonectes kuhlii, Fejevarya limnocharis, Fejevarya limnocharis, and Limnonectes microdiscus) with a difference in the number of species of 5 species between the rainy and dry seasons such as (Leptobrachium haseltii, Duttaphrynus melanostictus, Leptophyryne cruentata, Philautus aurifasciatus, and Nycxtixalus margaritifer).